INDONESIAN SMEs' ATTITUDE TOWARD INTERNET USAGE AS A PREREQUISITE OF INDUSTRY 4.0 TECHNOLOGY ADOPTION - Joseph, Abimana; Suryadi, Dedy (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Indonesia has been experiencing rapid economic growth over the past few years, driven by small and medium-sized enterprises (SMEs). However, with the advent of Industry 4.0 and the Internet of Things (IoT), SMEs must adopt and embrace new technologies to remain competitive. The changes directed scholars to study the adaptability and impact of those technologies on the organization’s efficiency; however, none has provided the roadmap for Indonesian SMEs to adopt Industry 4.0. Thus, the current research examines the preparedness of Indonesian SMEs’ adaptability to Industry 4.0 by analyzing the impact of SMEs’ capability and pillar enablers to use the internet as a prerequisite for adoption. The research uses secondary data named Sakernas with 215034 respondents. The structural equation modeling model was built based on SMEs’ capability, pillar enabler, and attitude to use the internet and was tested through computer software. The results show that both the SMEs' Capability (Number of Employees, Employee Education Level, and Revenue) and Pillar Enabler (Use of Digital Technology, Training, and Productivity) positively correlate with Internet use in communication and Promotion with a weight of 0.18 and 0.06 respectively while the P-value is below 0.001. Hence, Indonesian SMEs interested in stepping into the Industry 4.0 paradigm must eventually embrace the Internet first and then IoT to build the bridge to implement Industry 4.0.